PRESENTATION OF THE DOSSIER: INTERSECTIONALITY AND EDUCATION: CHALLENGES FOR THINKING ABOUT SCHOOL EDUCATION (Interdisciplinary Studies Journal, 2024)
The theory of intersectionality emerges as a crucial tool for a deep and multifaceted understanding of social reality, especially in the intricate educational context. By encompassing social markers such as class, race, gender, and various identity categories, intersectionality provides a more comprehensive and sensitive insight into the experiences, lives, and educational processes of individuals in the school environment. The school, as a central institution in shaping society, often inadvertently contributes to the reproduction of social inequalities by not recognizing and adequately addressing the singularities that deviate from the pre-established model.This dossier aims to delve into how intersectionality can shed light on the nuances in daily school life, influencing not only the construction of curricula but also the development of educational public policies and opening up new transformative perspectives for education in Brazil. By emphasizing the importance of intersectionality in the educational context, this dossier invited researchers to share their studies and reflections, exploring theoretical approaches grounded in this perspective and their practical application in formal education.The works in this dossier problematize educational practices and policies through the lens of intersectionality, as well as reflections on strategies to promote inclusive education that recognizes and respects the multiplicity of identities in Brazilian schools. Thus, our goal is to foster a broad and diversified dialogue on how intersectionality can guide new practices and educational policies in Brazil, pointing towards the construction of a more comprehensive school curriculum and fairer, more inclusive educational public policies.
Keywords: Intersectionality; Schooling; Dossier